Die Rolle der Klimaszenarienanalyse in der Wirkungsforschung - Bach, Wilfried (ERDKUNDE, 1985)
Man’s activities have reached proportions which can have adverse impacts on climate. These can be assessed indirectly by using warm world scenarios as analogs of a future warmer world, or more directly by climate model-derived scenarios driven by CO2and other forcing functions. In this paper emphasis is placed on developing climate scenarios from general circulation models as a basis for impact research. It is made clear that such climate scenarios should neither be construed as predictions of regional climatic change nor as forecasts of forthcoming climatic events, but rather as a set of self-consistent and plausible patterns of climatic change. Irrespective of the inherent uncertainties it is important to continue with the development of the appropriat methodology so that the scenario-derived climatic input ist available for impact analysis when it is needed. The ultimate goal is community preparedness, i.e. to have available an optimal strategy that can respond with flexibility to potential climatic risks.